EXPLORING EFL TEACHERS' FORMATIVE ASSESSMENT LITERACY: AN IN-DEPTH INVESTIGATION - Hidayat, M. Fadhil; Purnawarman, Pupung (STKIP Siliwangi, 2024)
The usefulness of formative assessment in a teaching process is widely recognized, but there hasn’t been much attention paid on examining teachers’ literacy in formative assessment. Therefore, this study aims to investigate teacher’s literacy of formative assessment, namely conceptual, practical, and socio-emotional dimensions. The study employed a qualitative approach, using semi-structured interview that was adapted from Yan & Pastore (2022b) to collect data from two English private primary school teachers. Thematic analysis by Miles & Hubberman (1994) was applied to examine the interview data. The findings indicated that the teachers possess a significant literacy in formative assessment. They provided a comprehensive explanation of their understanding, practices, and beliefs regarding formative assessment. Conceptually, they demonstrate a solid grasp of formative assessment principles. Practically, they effectively implement key strategies associated with formative assessment. Socio-emotionally, they exhibit a positive attitude towards formative assessment, recognizing its impact and highlighting the significance of fostering a mutual understanding between teachers and students. This paper offers valuable insights, enhances understanding, and provides a foundation for assessment courses and professional development.